Acute and sub-acute, double-blind, placebo-controlled studies on the effects of S-adenosyl- l-methionine on information processing by ERP-mapping and LORETA - Anderer, P.; Saletu, B.; Semlitsch, H.V.; Assandri, A.; DiPadova, C.; Prause, W.; Lindeck-Pozza, E.; Saletu-Zyhlarz, G.M. (International Congress series, 2002)
The effects of S-adenosyl- l-methionine (SAMe)—a naturally occurring molecule with antidepressant properties—on event-related potentials (ERPs) were investigated in normal healthy volunteers (10 young subjects aged 22–33 years and 10 elderly subjects aged 56–71 years). In random order, they received infusions of 800 mg SAMe in 250 ml of isotonic solution, and placebo, administered over 30 min for 7 days, with a wash-out period of 3 weeks in between. ERP recordings were carried out before and 1 h after drug administration on days one and seven in a two-tone odd-ball paradigm. Independent of the subjects' age, standard N1 latency was shortened after SAMe as compared to placebo and target P300 latency was lengthened. As revealed by means of low-resolution brain electromagnetic tomography (LORETA), there was an increase in N2 source strength in the temporal gyri and in P300 source strength prefrontally, left more than right. These ERP findings suggest both excitatory and inhibitory drug effects on perceptual and central information processing resources, which is typical for imipramine-type antidepressants and in accordance with our pharmaco-EEG results. Moreover, LORETA demonstrated drug-induced source strength increases in the (left) prefrontal cortex, a brain region in which PET studies revealed reduced blood flow and metabolism in depressed patients.